Treatment outcome differences between pass and fail scores and correlation between cephalometric changes and cast-radiograph evaluation of the American Board of Orthodontics - Siew Peng Neoh; Chulaluk Komoltri; Nita Viwattanatipa (Wolters Kluwer Medknow Publications, 2018)
OBJECTIVE: Using the cast-radiograph evaluation (CRE) score of the American Board of Orthodontics (ABO), the purpose of this study was 1) to find the post-treatment discrepancies that contributed to low-quality outcomes and 2) to identify if there might be any correlation between cephalometric changes and post-treatment discrepancies. MATERIALS AND METHODS: About 200 records submitted for the Thai Board of Orthodontics examination were analyzed. Overall, 23 parameters of the CRE scores and 12 cephalometric changes were collected. Based on the total CRE score, the cases were classified into three categories: pass (score <20), undetermined (score 20-30), and fail (score >30). Kruskall-Wallis was used to analyze the differences of mean CRE scores among these three categories. In addition, the cases were further classified into fixed appliance, two-phase and orthognathic surgery groups. Correlation tests were carried out to determine if there might be any association between cephalometric changes and CRE parameters. RESULTS: Significant differences of mean CRE scores were found for all CRE components except interproximal contacts. Significant correlation coefficients with the total CRE scores were found for all parameters except interproximal contacts. Significant moderate association was found between lower incisor changes and CRE scores in the two-phase and orthognathic surgery group. CONCLUSIONS: In order to improve treatment outcome quality, the top four parameters that orthodontists should pay attention to are occlusal contacts, occlusal relationship, marginal ridges, and alignment and rotations. Cephalometric changes were not suitable as weighting factors for total CRE scores.